Gender - Diversity - Intersectionality (New) Perspectives in Adult Education - Endepohls-Ulpe, Martina; Ostrouch-Kaminska, Joanna (Waxmann, 2019)
Gender is a category with far-reaching consequences on educational processes which have been extensively investigated in the last decades. But current political situations and societal developments such as globalization or movement of refugees require to broaden the perspectives in gender research. The volume aims at giving an insight into attempts to cope with these new challenges particularly in adult education. The articles of this book have been reviewed by Prof. Elisabeth Sander and Prof. Astrid M czkowska-Christiansen.